The role of social work in managing family disputes in Druze sectarian courts in lebanon: Reality and challenges - Hakim, Ghada Osmat El; Mansour, Rania Mohamad (Edelweiss Applied Science and Technology, 2024)
This study seeks to underscore the critical importance of the specialized "Family Office" within the Druze sect’s religious courts and its essential role in addressing family disputes, particularly marital conflicts. It delves into both the theoretical framework and practical applications of the office’s functions, emphasizing the methodologies and mechanisms employed to resolve disputes in alignment with the cultural and legal nuances of the sect. Employing a phenomenological qualitative methodology, the study includes field interviews with judges, lawyers, social workers, and individuals directly impacted by marital disputes, aiming to explore their insights and experiences regarding the Family Office’s effectiveness. The findings aspire to provide well-founded recommendations for crafting innovative, scientifically grounded strategies to manage family disputes, ensuring they meet the diverse needs of all stakeholders while solidifying the Family Office’s position as a fundamental entity in the efficient resolution of conflicts within the judicial system.